Preparation of zirconia‐doped titania superacid and its application in viscosity reduction of heavy oil. (1st February 2016) - Li, Yiguang; Liu, Xueliang; Li, Xiaohong; Zhang, Zhijun; Zhao, Mengyun; Su, Changming
Abstract : Sulphated titania superacid (denoted as SO4 2− /TiO2 ) and sulphated zirconia‐doped titania superacid (denoted as SO4 2− /ZrO2 /TiO2 ) were prepared via a liquid‐phase in‐situ method. As‐prepared SO4 2− /TiO2 and SO4 2− /ZrO2 /TiO2 superacids were characterised by transmission electron microscopy, field emission scanning electron microscopy, X‐ray diffraction and Fourier transform infrared spectrometry. Moreover, the catalytic performance of SO4 2− /TiO2 and SO4 2− /ZrO2 /TiO2 for the aquathermolysis reaction and viscosity reduction of the extra‐heavy oil recovered at Shengli Oilfield (Dongying, China) was investigated. It was found that SO4 2− /TiO2 and SO4 2− /ZrO2 /TiO2 as the catalysts for the aquathermolysis process of the tested extra‐heavy oil have good catalytic performance. Saturated hydrocarbon, aromatic hydrocarbon, resin and asphalt composition of the tested heavy oil sample before and after aquathermolysis reaction indicates that the amount of the saturated hydrocarbon and aromatic hydrocarbon are increased, while the amount of resin and asphalt are decreased, showing promising potential in the industrial production of heavy crude oil.